(untitled) (Environmental Smoke, 2023)
In 2022, there have been several instances of the attempted damage to or destruction of high-value (cultural and economic) objects of art as a form of climate activism. In this letter, it is argued that the destruction of, or attempts to destroy, property is not a peaceful form of protest, and may constitute a criminal act. If unique art were to be destroyed through an act of climate activism, that would result in an irretrievable loss of profoundly important cultural icons. Moreover, activists may – through their destructive actions – land up irreversibly changing the culture of the appreciation of art. Even though these acts manage to garner global attention, it is argued that there are other productive non-destructive ways of drawing widespread attention to issues related to climate change without harming humanity’s precious cultural commodities.